LITERALISME SALAFI DALAM MEMAKNAI JIHAD - Musawar, Musawar (JURNAL PENELITIAN KEISLAMAN, 2012)
Jihad in Islam is understood in various ways by Muslims, including the Salafi Congregation. The group is seen as a group that understands the concept of jihad literally, so it is assumed to have a relationship with the idea of radicalism in Indonesia. To explore this problem, library research is used with content analysis approach. The results showed that in giving interpretations of jihad, Salafi applied textual interpretation, i.e. according to the meaning of the text. Therefore, jihad for the Salafi is divided into jihad t}alab and jihad difaâ. In the case of jihad thalab (attack), Salafiâs attitude is divided into two: Salafi Yamani who hold the view that jihad is not necessary t}alab (attack) not even be in the way of bombing. As for Salafi Jihadists, the war is still going on against âenemies of Islamâ, then any way to do is permitted including terror. On the other hand, jihad difaâ is defensive when attacked by another group.